2013
DOI: 10.1590/s0080-623420130000500013
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient safety: how and why incidences occur in nursing care

Abstract: RESUMENInvestigación cuantitativa de tipo transversal que analizó los incidentes relacionados a los cuidados de enfermería, por medio de la metodología del análisis causa -raíz. Fue realizado en una unidad de cuidados intensivos de un hospital público de Santiago de Chile. El universo fue compuesto por 18 incidentes relacionados a los cuidados de enfermería ocurridos de enero a marzo del 2012. La muestra fue constituida por seis casos relacionados a medicamentos y retiro no planificado de artefactos terapéutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
0
8
0
7
Order By: Relevance
“…Following the notification there are a series of interlinked actions: analyzing the event and the risk situation, directing learning aimed at improving the safety of patients during their hospitalization (25) . It is a systematic process that analyzes the factors that contribute to an incident, identified by reconstructing the sequence of events and by the constant questioning of its occurrence until its elucidation; a tool that needs to be better used to ensure patient safety, assisting in the actions to be taken to reduce and manage future damage (27) . Therefore, just notifying is not enough; in addition, managers must outline a process to analyze the data, to give feedback to the team and to proactively insert changes.…”
Section: Discussionmentioning
confidence: 99%
“…Following the notification there are a series of interlinked actions: analyzing the event and the risk situation, directing learning aimed at improving the safety of patients during their hospitalization (25) . It is a systematic process that analyzes the factors that contribute to an incident, identified by reconstructing the sequence of events and by the constant questioning of its occurrence until its elucidation; a tool that needs to be better used to ensure patient safety, assisting in the actions to be taken to reduce and manage future damage (27) . Therefore, just notifying is not enough; in addition, managers must outline a process to analyze the data, to give feedback to the team and to proactively insert changes.…”
Section: Discussionmentioning
confidence: 99%
“…There is still great difficulty accepting the error, fearing the punishment and the incomprehension of the community. The safety culture should be adapted to legal standards, since safe handling requires change of thoughts and use of appropriate records, one of the great problems of nursing practice (15,(37)(38) . Thus, we highlight the need for the adoption of a culture of safety in all institutions, allowing the team to feel safe when reporting errors, since it is only through knowledge about adverse events that it will be possible to understand the situation appropriately, exploring the adoption of truly effective preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…They also identified deficit in compliance with rules and institutional routines, nursing supervision deficit and professional inexperience as the main factors that contributed to the occurrence of adverse events (15) . In Sao Paulo, a study identified the factors that can lead to the occurrence of adverse events in surgical patients, according to the nursing staff: no conference of patient identification with surgical notice and surgical chart (80.6%), no conference of materials and equipment used in the procedures (80.7%), medical staff reprisals when alerting potential issues (71%) and omission of the nursing team because of the lack of leader autonomy (71%) (16) .…”
Section: Main Causes Of Adverse Events In Nursing Carementioning
confidence: 99%
“…Esse risco é aumentado na medida em que os profissionais de saúde não são capazes de ler corretamente as prescrições, resultando em confusão durante a dispensação, distribuição, preparo e administração. Por conseguinte, um dos fatores que podem auxiliar na prevenção desses eventos é a correta identificação do paciente, uma vez que clientes com nomes semelhantes, em mesma enfermaria ou recebendo o mesmo medicamento, porém com doses diferenciadas, podem ser facilmente confundidos, passando a receber uma dose inadequada para o seu tratamento (10)(11)(12)(13)(14) .…”
Section: Discussionunclassified